2017
DOI: 10.3141/2670-01
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Drivers’ Attitudes Toward Use of Electronic Toll Collection Systems in Spain

Abstract: Electronic payment is increasing inexorably as a means of paying for the use of toll roads worldwide. However, it is necessary to increase the effectiveness and expediency of this mechanism, as well as improve policy issues such as privacy or data management. The state of the art in this field typically analyzes users’ perceptions and willingness to pay to use toll roads. However, research addressing drivers’ attitudes toward the use of electronic toll collection (ETC) systems is not sufficiently developed. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Chang et al pointed out that the implementation of ETC on expressways can provide more flexible solutions for road pricing, and they developed a road pricing model to promote a win-win situation among stakeholders [25]. Heras-Molina et al found that free tagging equipment is an effective policy measure to encourage individuals to use ETC and additional toll roads [26]. Al-Deek et al proposed a microscopic simulation model, which is specifically developed for evaluating the operating performance of toll stations.…”
Section: Introductionmentioning
confidence: 99%
“…Chang et al pointed out that the implementation of ETC on expressways can provide more flexible solutions for road pricing, and they developed a road pricing model to promote a win-win situation among stakeholders [25]. Heras-Molina et al found that free tagging equipment is an effective policy measure to encourage individuals to use ETC and additional toll roads [26]. Al-Deek et al proposed a microscopic simulation model, which is specifically developed for evaluating the operating performance of toll stations.…”
Section: Introductionmentioning
confidence: 99%